Metabolic reprogramming of macrophages in chronic obstructive pulmonary disease - Qin, Ziwen; Liu, Wenjuan; Huang, Chuanjun; Zhang, Wei (Frontiers in Immunology, 2025)
Chronic obstructive pulmonary disease (COPD) is currently one of the major causes of death and hospitalization globally. Pulmonary inflammation and oxidative stress are considered important mechanisms underlying the disease. Recent studies have indicated that the metabolic processes of immune cells in COPD, notably alveolar macrophages (AMs), may undergo significant alterations, exhibiting distinct metabolic characteristics related to their functional state and polarization phenotype. This phenomenon is known as the immunometabolic reprogramming of macrophages. In this article, we review the polarization phenotype and metabolic characteristics of macrophages in COPD, as well as the mechanisms affecting macrophage metabolism, and discuss the potential significance of pathways targeting immunometabolism of AMs in the treatment of COPD.